Kedudukan Hukum Perjanjian Kredit dalam Hal Objek Jaminan Fidusia Musnah - I Gusti Agung Mas Cahyani Dewi; Anak Agung Sagung Laksmi Dewi; Ni Made Puspasutari Ujianti (Warmadewa Press, 2020)
Crediting activities can be carried out by anyone who has the ability to initiate a loan agreement between the creditor / creditor and the recipient of the loan / debtor, this is regulated in article 8 of the Banking Act. This study aims to analyze the legal position in the credit agreement if the fiduciary collateral object is destroyed, and analyze efforts to resolve disputes due to the destruction of the fiduciary collateral object. The method used is an empirical method with the approach of legal sociology. The results showed that the legal position of the credit agreement if the fiduciary collateral object was destroyed either in the case that the object became the object had been insured or not insured by the owner of the object. The credit agreement remains and the debtor remains responsible for paying off the debt. With this situation, the creditor will turn into a concurrent creditor. Furthermore, in resolving disputes the destruction of fiduciary collateral objects, there are two ways, namely, if the object used as fiduciary collateral object by the debtor in a credit agreement is insured, the creditor can claim insurance for the collateralized object. Whereas if the object which is used as collateral has not been insured in this case the creditor has issued a credit and is taking care of the object's insurance, an undesirable event occurs by the debtor and the creditor, namely the destruction of the object used as collateral. Then the debtor must be held responsible by replacing the items pledged with new objects owned by the debtor and the selling price is the same as the credit issued by the creditor.